2021
DOI: 10.1093/cei/uxab010
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal anti-tissue transglutaminase IgA deposits as a complementary method for the diagnostic evaluation of celiac disease in patients with low-grade histological lesions

Abstract: Summary Evaluating the usefulness of intestinal anti-transglutaminase IgA (anti-TG2 IgA) deposits detection as a complementary or decision-supporting tool in the diagnosis of celiac disease (CD) in patients with low degree of enteropathy. Small intestinal biopsies (SIB) were performed from 2008 to 2017 in patients on suspicion of CD (positive CD serology and/or symptoms) referred to our Pediatric Gastroenterology Unit. We determined anti-TG2 IgA deposits by using double immunofluorescence in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In children with anti-TG-2 positivity lower than 10 times the upper limit, at least 4 biopsies from the distal duodenum and at least 1 from the bulb should however be taken ( 19 ). Recently, Roca et al ( 22 ) suggested the detection intestinal anti-TG2 deposits as a complementary or supporting tool for CD diagnosis in pediatric population with symptoms suggestive of CD and low-grade histological picture.…”
Section: Coeliac Diseasementioning
confidence: 99%
“…In children with anti-TG-2 positivity lower than 10 times the upper limit, at least 4 biopsies from the distal duodenum and at least 1 from the bulb should however be taken ( 19 ). Recently, Roca et al ( 22 ) suggested the detection intestinal anti-TG2 deposits as a complementary or supporting tool for CD diagnosis in pediatric population with symptoms suggestive of CD and low-grade histological picture.…”
Section: Coeliac Diseasementioning
confidence: 99%
“…Since anti-TG2 antibodies are produced at the intestinal mucosa level and only later spill off in blood vessels, methods to detect them in situ could have a diagnostic utility in situations of doubt (for example, in patients with negative serology) or when other approaches are inconclusive [ 105 , 106 ]. First detection of intestinal anti-TG2 antibodies is performed on faecal supernatants.…”
Section: Tg2 In CD Diagnosismentioning
confidence: 99%